Karakteristik Tepung Ikan Lemuru Dengan Variasi Perlakuan Pendahuluan - Rafika Aisyah Ananda; Didiek Hermanuadi; Aulia Brilliantina; Elok Kurnia Novita Sari; Syamsiar Kautsar; Putu Tessa Fadila (JOFE : Journal of Food Engineering, 2022)
A study has been conducted to utilize lemuru fish into fish meal products. This study aims to determine the appropriate processing method for the manufacture of lemuru fish meal products and to determine the physicochemical characteristics of lemuru fish meal. Lemuru fish are processed into fish meal with three different processing treatments, namely boiling, pressure steaming, and using temperature of 50˚C and 60˚C in each processing. The fish meal obtained was analyzed with parameters of water content, ash content, fat content, protein content and degree of whiteness according to the Indonesian National Standard SNI 01-2715-1996. The result of this study indicate that the best results from lemuru fish meal in the analysis of water content are boiling treatment with mabu 60˚C (5,24%), ash content of 50˚C temperature treatment (3,99%), protein content of 60˚C boiling treatment (49,41%), the fat content of the sub-boiling treatment was 60˚C (7%), and the degree of whiteness of the presto treatment been carried out is the boiling treatment using a temperature of 60˚C.